2007
DOI: 10.1101/gr.6531807
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis across a kingdom of eukaryotic organisms: Specialization and diversification in the Fungi

Abstract: The recent proliferation of genome sequencing in diverse fungal species has provided the first opportunity for comparative genome analysis across a eukaryotic kingdom. Here, we report a comparative study of 34 complete fungal genome sequences, representing a broad diversity of Ascomycete, Basidiomycete, and Zygomycete species. We have clustered all predicted protein-encoding gene sequences from these species to provide a means of investigating gene innovations, gene family expansions, protein family diversific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 76 publications
7
66
0
2
Order By: Relevance
“…Similar results were obtained with a scdA echA double mutant in Podospora anserina (4). Recent in silico surveys of the pathways encoded in more than 50 fungal genomes revealed that most fungi possess both mitochondrial and peroxisomal pathways (8,52).…”
supporting
confidence: 79%
“…Similar results were obtained with a scdA echA double mutant in Podospora anserina (4). Recent in silico surveys of the pathways encoded in more than 50 fungal genomes revealed that most fungi possess both mitochondrial and peroxisomal pathways (8,52).…”
supporting
confidence: 79%
“…Fungal ␤-oxidation is not well characterized, and it was previously thought that fungi might have peroxisomal ␤-oxidation only because Saccharomyces cerevisiae lacks the enzymes for mitochondrial ␤-oxidation (73,75). However, recent in silico surveys of the pathways encoded in more than 50 fungal genomes revealed that most fungi possess both mitochondrial and peroxisomal pathways (10,69). Mitochondrial ␤-oxidation has also been convincingly demonstrated in the saprophytic ascomycete Aspergillus nidulans (26,44,45).…”
Section: T He Basidiomycete Fungus Cryptococcus Neoformans Causes Menmentioning
confidence: 99%
“…The comparison of annotated genomes from many related species can highlight common core components of these signalling cascades, while global analyses of changes in gene expression under different environmental conditions and developmental stages can be used to identify downstream targets. However, comparative genomic studies of fungi are currently somewhat limited, due to the relative paucity of well-annotated fungal genomes and the large proportion of genes in fungi with no known function (Cornell et al, 2007;Soanes et al, 2007). Benefiting from advances in next-generation sequencing, this situation is likely to change with the routine use of affordable, massively parallel sequencing platforms such as the 454 from Roche, the Applied Biosystems SOLiD and the Illumina GA2.…”
Section: Introductionmentioning
confidence: 99%